Single-Stage Revision Surgery in Infected Total Knee Arthroplasty: A PRISMA Systematic Review - Yaghmour, Khaled M. (J Clin Med, 2019)
Periprosthetic joint infection in total knee arthroplasty is a significant complication that is a common reason for revision surgery. The current standard of care is two-stage revision surgery. There is however increasing evidence to support the use of single-stage revision surgery. We conducted a PRISMA systematic review of the current evidence on the use of single-stage revision for infected total knee arthroplasty. Four databases (PubMed, Embase, Science Direct, and Cochrane Library) were systematically screened for eligible studies. The risk bias of each study was identified using ROBINS-I tool, and the quality of evidence was assessed using the GRADE criteria. Sixteen articles were retained after applying the inclusion and exclusion criteria that evaluated 3645 knee single-stage revision surgeries. Our review reveals satisfactory outcomes for single-stage revision in the management of infected total knee arthroplasty. The reinfection rates in the studies included in our review varied however the majority reported low reinfection rates and good functional outcomes. Although strict patient selection criteria have yielded successful results, good results were also reported when these criteria were not applied. The greater use of risk factors in identifying patients likely to have a successful outcome needs to be balanced with the practical benefits of performing a single stage procedure in higher risk patients. Future large clinical randomized control trials are required to confirm our results.